Disease-modifying effects of phosphocitrate and phosphocitrate-β-ethyl ester on partial meniscectomy-induced osteoarthritis. Issue 1 (December 2015) - Sun, Yubo; Haines, Nikkole; Roberts, Andrea; Ruffolo, Michael; Mauerhan, David; Mihalko, Kim; Ingram, Jane; Cox, Michael; Hanley, Edward
Abstract Background It is believed that phosphocitrate (PC) exerts its disease-modifying effects on osteoarthritis (OA) by inhibiting the formation of crystals. However, recent findings suggest that PC exerts its disease-modifying effect, at least in part, through a crystal-independent action. This study sought to examine the disease-modifying effects of PC and its analogue PC-β-ethyl ester (PC-E) on partial meniscectomy-induced OA and the structure-activity relationship. Methods Calcification- and proliferation-inhibitory activities were examined in OA fibroblast-like synoviocytes (FLSs) culture. Disease-modifying effects were examined using Hartley guinea pigs undergoing partial meniscectomy. Cartilage degeneration was examined with Indian ink, safranin-O, and picrosirius red. Levels of matrix metalloproteinase-13 (MMP-13), ADAM metallopeptidase with thrombospondin type 1 motif 5 (ADAMTS5), chemokine (C-C motif) ligand 5 (CCL5), and cyclooxygenase-2 (Cox-2) were examined with immunostaining. The effects of PC-E and PC on gene expressions in OA FLSs were examined with microarray. Results are expressed as mean ± standard deviation and analyzed using Student'st test or Wilcoxon rank sum test. Results PC-E was slightly less powerful than PC as a calcification inhibitor but as powerful as PC in the inhibition of OA FLSs proliferation. PC significantly inhibited cartilage degeneration in the partial meniscectomied right knee. PC-E was less powerful than PC as a disease-modifying drug, especially in the inhibition of cartilage degeneration in the non-operated left knee. PC significantly reduced the levels of ADAMTS5, MMP-13 and CCL5, whereas PC-E reduced the levels of ADAMTS5 and CCL5. Microarray analyses revealed that PC-E failed to downregulate the expression of many PC-downregulated genes classified in angiogenesis and inflammatory response. Conclusions PC is a disease-modifying drug for posttraumatic OA therapy. PC exerts its disease-modifying effect through two independent actions: inhibiting pathological calcification and modulating the expression of many genes implicated in OA. The β-carboxyl group of PC plays an important role in the inhibition of cartilage degeneration, little role in the inhibition of FLSs proliferation, and a moderate role in the inhibition of FLSs-mediated calcification.